The Influence of Job Insecurity and Career Development on Employee Loyalty at Informa PTC Palembang - Welly, Muhammad; Roswaty, Roswaty; Purnamasari, Endah Dewi (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the influence of job insecurity and career development on employee loyalty at Informa PTC Palembang. The research employs a quantitative approach with a saturated sampling technique, where all 95 employees in the population were included as respondents. Data were collected through questionnaires and analyzed using statistical tests, including partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²). The results indicate that job insecurity and career development significantly influence employee loyalty both partially and simultaneously. The coefficient of determination shows that 27.9% of the variation in employee loyalty is explained by these variables, while the remaining 72.1% is influenced by other factors outside the research model. The findings suggest that the company should focus on managing job insecurity and strengthening career development programs to enhance employee loyalty Keywords : Job Insecurity, Career Development, Employee Loyalty